Genome‐wide analysis identifies gallstone‐susceptibility loci including genes regulating gastrointestinal motility. Issue 5 (10th December 2021) - Fairfield, Cameron J.; Drake, Thomas M.; Pius, Riinu; Bretherick, Andrew D.; Campbell, Archie; Clark, David W.; Fallowfield, Jonathan A.; Hayward, Caroline; Henderson, Neil C.; Iakovliev, Andrii; Joshi, Peter K.; Mills, Nicholas L.; et al.
Abstract: Background and Aims: Genome‐wide association studies (GWAS) have identified several risk loci for gallstone disease. As with most polygenic traits, it is likely that many genetic determinants are undiscovered. The aim of this study was to identify genetic variants that represent new targets for gallstone research and treatment. Approach and Results: We performed a GWAS of 28, 627 gallstone cases and 348, 373 controls in the UK Biobank, replicated findings in a Scottish cohort (1089 cases, 5228 controls), and conducted a GWA meta‐analysis (43, 639 cases, 506, 798 controls) with the FinnGen cohort. We assessed pathway enrichment using gene‐based then gene‐set analysis and tissue expression of identified genes in Genotype‐Tissue Expression project data. We constructed a polygenic risk score (PRS) and evaluated phenotypic traits associated with the score. Seventy‐five risk loci were identified ( p  < 5 × 10 −8 ), of which 46 were new. Pathway enrichment revealed associations with lipid homeostasis, glucuronidation, phospholipid metabolism, and gastrointestinal motility. Anoctamin 1 ( ANO1 ) and transmembrane Protein 147 ( TMEM147 ), both in novel, replicated loci, are expressed in the gallbladder and gastrointestinal tract. Both regulate gastrointestinal motility. The gallstone risk allele rs7599‐A leads to suppression of hepatic TMEM147 expression, suggesting that the protein protects against gallstone formation. The highest decile of the PRS demonstrated a 6‐fold increased odds of gallstones compared with the lowest decile. The PRS was strongly associated with increased body mass index, serum liver enzymes, and C‐reactive protein concentrations, and decreased lipoprotein cholesterol concentrations. Conclusions: This GWAS demonstrates the polygenic nature of gallstone risk and identifies 46 novel susceptibility loci. We implicate genes influencing gastrointestinal motility in the pathogenesis of gallstones. Abstract : image